Aplikasi Komputer dan Smartphone Berbasis Android untuk Menangani Reservasi Hotel pada Citi Smart Hotel - BSD - Ari Abdilah; Elva Mardiyani; Imam Nawawi (Universitas Bina Sarana Informatika, 2018)
Presentation of information the availability rooms still manual is one of the problems experienced by Citi Smart Hotel for visitors to come to the hotel or reservation via telephone to know the availability room. It will be wasting visitor time to come to the hotel and just asking availability room and then make a reservation. This needs to made to a reservation system that can provide more detailed information on bookings and availability rooms in hotel, then built the application of a reservation hotel room based Android. This application running on a platform Android and integrating with applications residing on the server. This research talk about the design and the implementation of the application of a reservation system hotel room based Android. Through the application of this reservation, it is expected that the transaction a reservation can be done anywhere and anytime without bound with time and appropriate place the cost of also by the visitor.